Survey on Implementation of Adaptive Physical Education Learning in Extraordinary Schools in Aceh Tenggara Regency - Afrizal Afrizal; Fakhrur Rizal (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
All special schools in Aceh Tenggara Regency have implemented physical education subjects, but the implementation of physical education subjects has not been carried out well until now. When viewed from an effective and efficient teaching and learning process, all teachers who teach physical education at the Special School of Southeast Aceh Regency, still encounter many obstacles and obstacles in the teaching and learning process of physical education, this is mainly due to the majority of teachers who teach Physical education has an educational background that is not physical education, different forms of disability from all students, inadequate facilities and infrastructure and available teaching media, lack of references to educational guidebooks. Whereas, it is very much needed by teachers who teach education in supporting the teaching and learning process.